Pengaruh Motvasi Kerja, Budaya Organisasi Dan Komitmen Organisasi Terhadap Kinerja Pegawai (Pada Badan Kepegawaian Dan Pengembangan Sumber Daya Manusia Kota Malang) - Bayu Kristianingsih; Hadi Sunaryo; Khalikussabir Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
ABSTRACTThis research was conducted to determine the effect of work motivation, organizational culture and organizational commitment on employee performance at the Agency for Personnel and Human Resources Development in Malang. The method used is quantitative. The sample used in this study was 44 employees, the method of data collection using primary and secondary data. using saturated sampling, so get 44 respondents who aim to explain the position of each variable and its influence between one variable with another variable, and the source of the data used is primary data by distributing questionnaires to employees of the BKPSDM Agency in Malang. The results of this study are the variables of work motivation, organizational culture, and organizational commitment simultaneously and partially influence employee performance. Keywords: Work motivation, organizational culture, organizational commitment, performance